2001
DOI: 10.1038/ni722
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell maturation is required for the cross-tolerization of CD8+ T cells

Abstract: In vivo models have shown that tissue-restricted antigen may be captured by bone marrow-derived cells and cross-presented for the tolerization of CD8+ T cells. Although these studies have shown peripheral tolerization of CD8+ T cells, the mechanism of antigen transfer and the nature of the antigen-presenting cell (APC) remain undefined. We report here the establishment of an in vitro system for the study of cross-tolerance and show that dendritic cells (DCs) phagocytose apoptotic cells and tolerize antigen-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
275
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(290 citation statements)
references
References 37 publications
10
275
0
5
Order By: Relevance
“…but the cells apoptose and/or fail to accumulate (50,51). Proliferation leading to accumulation in the absence of effector function has been described for CD8 T cells activated by artificial APC (52).…”
Section: Discussionmentioning
confidence: 99%
“…but the cells apoptose and/or fail to accumulate (50,51). Proliferation leading to accumulation in the absence of effector function has been described for CD8 T cells activated by artificial APC (52).…”
Section: Discussionmentioning
confidence: 99%
“…These immature DCs express lower levels of major histocompatibility complex molecules and lack the expression of co-stimulatory molecules at the time of antigen presentation. There is evidence, however, that mature APCs can also induce tolerance (Albert et al, 2001;Menges et al, 2002). We have shown that IDOexpressing APCs, both immature and mature, inhibit antigen-driven proliferation of lymphocytes in mixedleukocyte reactions .…”
Section: Lee Et Almentioning
confidence: 99%
“…There is increasing evidence that antigen presentation by certain bone marrow-derived antigenpresenting cells (APCs) is an important initiator of immunologic self-tolerance (Albert et al, 2001;Dhodapkar et al, 2001;Doan et al, 2000;Jonuleit et al, 2001;Pardoll, 2001;Sotomayor et al, 2001;Steinman and Nussenzwieg, 2002). The characterization of these cells and the mechanism of in vivo tolerance induction, however, is still elusive.…”
mentioning
confidence: 99%
“…In particular, CD4 ϩ T cells have been shown to play a critical role in tumor eradication when CD8 ϩ T cell numbers are suboptimal (21), to be involved in both CD8 ϩ T cell maintenance and tumor mass infiltration (22), to be important for the recruitment of antitumor effector cells to the tumor mass (23), as well as to have direct antitumor effector functions (24). CD4 ϩ T cells have also been shown to be important for the maturation of DC, a process critical for the effective activation of the Ag-specific CD8 ϩ T cell compartment (25). Finally, the activation of tumor Ag-specific CD4 ϩ T cell help is an important prerequisite for the subsequent development of a humoral antitumor response.…”
Section: Discussionmentioning
confidence: 99%